Empowering a Knowledge-Based Economy: An Assessment of the Influence on Economic Development - GODUNI, Jonida (Theoretical and Practical Research in Economic Fields; Vol 15 No 3 (2024): TPREF, Volume XV, Issue 3(31), Fall 2024, 2024)
Scientific research is one of the most important variables affecting the economic growth and development of a country, being the engine of innovation. In this regard, the relevance of various assessments of scientific interaction with economic development is determined by modern requirements. The study aims to investigate the impact of scientific research on economic development in Albania. The assessment was based on the analysis of secondary data from organisations such as Eurostat and INSTAT, which were further considered within the framework of an econometric model in EViews. The study highlighted the role of stimulating economic development in Albania in various sectors. The study demonstrated that scientific research is highly significant for the economic growth of a country. Based on the statistical data during the period from 1996 to 2022, a regression model was employed to simulate the relationship between independent variables (scientific labour force, public research and development (R&D) expenditures, and patents) and the dependent variable (gross domestic product (GDP) growth). The study shows that these factors have a positive impact on the gross domestic product per capita in Albania. The empirical research results revealed that the scientific labour force, public R&D expenditures and patents have a positive and significant impact on GDP growth in Albania. Based on the information received, recommendations were made to improve the quality of scientific research in the country. The result of this study could provide valuable information to policymakers and serve as scientific evidence for future studies.